Al-Chemy: e-learning platform for foundation students - Nur Ilyana Ismarau Tajuddin; Nurul Jannah Abd Rahman; Khairi Azhar Aziz; Noorrezam Yusop; Nor Aziyatul Izni (Bulletin of Electrical Engineering and Informatics, 2023)
The unexpected closure of educational institutions as a result of the emergence of COVID-19 prompted the authorities to suggest adopting alternatives to traditional learning methods. E-learning is an innovative approach for delivering electronically mediated, well-designed, learner-centred interactive learning environments by utilizing internet and digital technologies with respect to instructional design principles. This paper presents the implementation and prototyping of an innovative web-based e-learning platform for chemistry course known as Al-Chemy. Al-Chemy was developed for foundation students at Tahmidi Centre, Universiti Sains Islam Malaysia. The rapid application development (RAD) methods have been used in developing Al-Chemy through website wix.com. Al-Chemy was structured with interactive notes, animation, virtual experiment, quizzes, and games. The combination of these activities helps students in learning basic and advanced concepts of chemistry.